Bridging the gap between corporate social responsibility and new green product success: The role of green organizational identity. (26th July 2018) - Song, Wenhao; Ren, Shengce; Yu, Jun
Abstract: In this study we explore the relationship between corporate social responsibility and new green product success based on organizational identity theory. The hypotheses are tested on a sample of 150 companies in China. The results indicate that corporate social responsibility positively affects both green organizational identity and green adaptive ability. We also find that green organizational identity and green adaptive ability are positively influences on new green product success. In addition, we find that green organizational identity partially mediates the relationship between corporate social responsibility and green adaptive ability. Moreover, green organizational identity fully mediates the link between corporate social responsibility and new green product success. This means that corporate social responsibility indirectly and positively affects new green product success through green organizational identity. These results suggest that managers should seek to enhance their organizational sense of green identity and improve their organizational green adaptive ability, which will facilitate their firm's sustainable development. The theoretical and practical implications of these findings for environmental policy are also discussed.